Anti-müllerian hormone levels and antral follicle count in women with a BRCA1 or BRCA2 germline pathogenic variant: A retrospective cohort study - Denis-Laroque, Laurie (Breast, 2021)
BACKGROUND: Some studies suggested a decreased ovarian reserve among BRCA1/2 pathogenic variant carriers, with conflicting results. METHODS: We conducted a retrospective single-center observational study of ovarian reserve and spontaneous fertility comparing BRCA1/2 pathogenic variant carriers to controls (women who attended consultations to discuss fertility preservation before gonadotoxic treatment). Measures of associations between plasma AMH concentration, AFC and BRCA1/2 status were modelled by nonlinear generalized additive regression models and logistic regressions adjusted for age at plasma storage, oral contraceptive use, body mass index, cigarette smoking, and the AMH assay technique. RESULTS: The whole population comprised 119 BRCA1/2 pathogenic variant carriers and 92 controls. A total of 110 women (42 carriers, among whom 30 were cancer-free, and 68 controls) underwent an ovarian reserve evaluation. Spontaneous fertility analysis included all women who previously attempted to become pregnant (134 women). We observed a tendency towards a premature decrease in ovarian reserve in BRCA1/2 pathogenic variant carriers, but no difference in mean AMH or AFC levels was found between BRCA1/2 pathogenic variant carriers and controls. An analysis of the extreme levels of AMH (≤5 pmol/l) and AFC (≤7 follicles) by logistic regression suggested a higher risk of low ovarian reserve among BRCA1/2 pathogenic variant carriers (adjusted odds ratio (OR) = 3.57, 95% CI = 1.00–12.8, p = 0.05; and adjusted OR = 4.99, 95% CI = 1.10–22.62, p = 0.04, respectively). DISCUSSION: Attention should be paid to BRCA1/2 pathogenic variant carriers’ ovarian reserve, considering this potential risk of premature alteration.